K12 Supporting youth affected by HD: results from the north american youth summer camp evaluation. (13th September 2016) - Kavanaugh, Melinda; Swope, Chandler; Ellison, Matthew
Abstract : Background: Health related youth respite camps traditionally target the youth with an illness or disability (cancer, diabetes, Downs syndrome etc), providing support, guidance and disease based education. However, little published evaluation data exists on effect of camps that serve youth with a parental or other family illness. Living in a family with chronic or acute illness impacts the child well-being, stress levels and isolation from youth not tasked with dealing with an ill family member. This paper provides evaluation data on one unique camp in North America, targeting children and youth who have a family member with Huntington's disease (HD). The North American HD Youth Summer Camp was designed to provide young people ages 15–23 a break from home life and an opportunity to gain peer and professional support around HD issues and HD education. Through a mix of activities and educational sessions, the camp offers young people the opportunity to build coping skills, peer relations, support and HD education. Campers must have a parent/family member with Huntington's disease, live in the US or Canada, and complete an application. A total of 55 applications were received and all offered admission. 45 campers were accepted. All gender, races, and ethnicities were eligible for inclusion in attending the camp. Aims: To describe the impact of the first North American camp on several measures of youth well-being in youths who have a family member affected by HD. Specific research questions addressed: 1) Do youth report an increase in knowledge about HD and support in dealing with HD; 2) Are resilience, self-esteem, and life satisfaction increased as a function of attending the camp? Methods: The camp evaluation consisted of a survey administered at four time points, 6-weeks baseline, pre camp, post camp and 6-weeks post, assessing differences in self-esteem, social support, resilience, health related quality of life, and HD issues. Results/outcome: At total of 35 campers completed the pre-camp survey (23 = female, 12 = male), range from 14 to 23, with average age 18. Campers are predominately white (N = 33) and from the US (N = 29). Campers describe isolation from friends (N = 24), felling less "normal" than other kids (N = 22), having not enough information about testing (N = 25), or relationships and HD (N = 13). Only four had any contact with an HD organisation (HDYO, HDSA or HSC). Female participants increased their self-esteem score significantly from baseline to post-camp by 0.28 (SE = 0.08, p = 0.013), and overall camp participants' life satisfaction score changed significantly throughout the study (p < 0.001). Results show an overall significant increase in social support across time for all participants (p = 0.019). Conclusions: Findings from the study suggest youth affected by HD are an isolated group, in need of not only HD specific information, but also support around issues of self-esteem and well-being. These results highlight the stated goals of the camp, to provide support and education, while underscoring the need for the provision of HD youth focused programming.